Efficacy of tranexamic acid in haemoptysis: A randomized, controlled pilot study. (October 2016) - Bellam, Balaji Laxminarayanshetty; Dhibar, Deba Prasad; Suri, Vikas; Sharma, Navneet; Varma, Subhash Chander; Malhotra, Samir; Bhalla, Ashish
Abstract: Back ground: Haemoptysis is a life threatening condition irrespective of aetiology. Tranexamic acid (TA), a potent anti-fibrinolytic agent, has been shown to control bleeding, decrease transfusion requirement in knee & hip arthroplasty, coronary artery bypass grafting and heavy menstrual bleeding. TA also has mortality benefit in bleeding from surgical and trauma patients. But the studies, regarding efficacy and safety of TA in controlling haemoptysis are conflicting. Method: In this single blinded, prospective study, total 66 patients with sub-massive haemoptysis were randomized into treatment (T) and placebo control (C) groups. Group-T received intravenous (IV) TA in a loading dose of 1 g, followed by 1 g TA over 8 h infusion and group-C received IV 0.9% normal saline. The severity of haemoptysis was assessed by quantity, frequency and visual analogue scale (VAS) score. Results: On day 2, frequency, quantity and VAS score of haemoptysis were 2.23 ± 2.11/day, 34.19 ± 67.0 ml and 14.72 ± 15.7 respectively in Group-T and 2.29 ± 2.0/day, 90.4 ± 79.0 ml and 31.33 ± 22.12 respectively in group-C. In group-T 16.27% patients needed intervention as compared to 38.1% in group-C (p 0.053). The mean blood transfusion (1.58 ± 0.88 & 1.67 ± 0.669 units) and hospital stay (4.14 ± 3.18 & 5.48 ± 3.26 days) was also lower in group-T as compared to group-C. Group-T had better outcomes as compared to group-C, but statistically significant only for VAS score (p 0.001). During study no adverse event of the drug was noted. Conclusion: TA decreases severity of haemoptysis and can be used as a bridging therapy in acute haemoptysis before definitive intervention can be under taken.